Kepariwisataan di masa krisis: kunjungan wisata pada masa pandemi covid-19 di pantai Pangandaran, Indonesia - Meitolo Hulu; Lidia Ariyanti (Journal of Tourism and Economic, 2022)
This study uses a qualitative approach by conducting interviews and observations of tourism business actors and visitors in Pangandaran beach tourism area. The focus of the study is on the difficulties faced by tourism business actors and explore the experience of visitors on Pangandaran beach during the Covid-19 pandemic. This research was conducted with a descriptive qualitative approach with primary and secondary data collection. Primary data collection was carried out through interviews and observations by adhering to strict health protocols. While secondary data is done through the collection of documents related to research studies online and offline. The results of this study indicate that the difficulties faced by tourism business actors in the Pangandaran coastal area during the Covid-19 pandemic are experiencing an economic decline and information uncertainty regarding the closure of tourism destinations. Meanwhile, visitors have difficulty accessing tourist destinations due to mobility restrictions in some areas. The policy of restricting access in several regions in Indonesia has a broad impact on other tourism destinations, and one of them is Pangandaran beach tourism area. It takes commitment from tourism businesses and awareness from visitors is the main key in implementing health protocols.